6 Answers | Add Yours
ax-b = c
Follow the same steps you would for following regular equations. Since the opposite of - b is + b, start by adding b to both sides.
ax - b + b = c + b
ax = c + b
Now since x is being multiplied by a, do the opposite and divide both sides by a
(ax)/a = (c + b)/a
x = (c + b)/a
1. The goal is to get x on a side of the = by itself.
2. In the original equation we have ax-b so to get the b on the other side of the = we have to +b.
3. That then gives us the equation ax=c+b
4. Next we have to remember that ax isa multiplication problem of a times x. So to get a to the other side we will have to divide both sides by a.
5.we then get x=(c+b)/a
Now we have the given equation as
[adding b on both side we have]
[dividing both side by a, we get]
so the value of x is (c+b)/a
here is one more in solving equations and formulas
15x + 1 = y for x
To solve a problem like ax-b=c for x, we normally have to go through the following steps.
Here a, b and c are numbers and x is an unknown oa variable.
ax-b=c is the equation to solve.
Add b to both sides.
Divide by a both sidesby a:
x=(b+c)/a is the solution.
Example : Solve 10x- 20 = 30.
Follow the above steps:
Add 20 to both sides.
Divide both sides by 10 :
x=5. So x=5 is the solution of 10x-20=30 by following the above steps.
We’ve answered 318,950 questions. We can answer yours, too.Ask a question